Homes Becoming Religious Transnational Spaces: The Impact of COVID-19 Immobility on the Religious Activities of Migrant Muslim Women - Ince-Beqo, Gül (Italian Sociological Review, 2024)
Since the outbreak of the COVID-19 emergency, the marked division between the home and public space has been increasingly emphasized, and the concept of ‘home’ has become more and more connoted with the values of security and control. The question that arises is this: how did the ‘stay-at-home’ period affect (and continues to affect) the home-based life of migrant Muslim women and their collective religious practices? Drawing upon the narratives of Turkish Muslim women living in Northern Italy, the research reported in this paper focused on their frequency of religious participation both during the pre-pandemic period and during the ‘stay-at-home’ one by identifying how they adapted to online meetings, courses, or collective prayers. If collective religious activity in mosques for these women, in addition to spiritual support, was a remarkable opportunity for them to interface with public space, allowing them to retreat from the everyday family commitments of their home, virtual participation in religious events organized by both the country of origin and the diasporas created a highly transnational dimension for them in that same home. Considering Italy’s peripheral diasporic position, particularly in terms of religious organizations, in the Turkish diaspora in Europe, this expanded, albeit virtual, participation of migrant women is significant because it seems to give them the opportunity to reinvent the meanings of place and the migratory experience, about both their peers in Turkey and to those living in the diasporas, and to develop awareness about identity issues.